(3GdJYOOjI GdSjGSjI hJOGhd GdSdWI Hjf GdfXGe GdSjGSi GdGSdGei hGdfXGe GdOjebQGWis (3OQGSI ebGQfI eY GdJWHjb (B/ s - (3UahJ GMeO YHOGdZfis; (3jMji GdLed (B: s; (3LGeYI GdbGgQI s (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb (B- (3LGeYI GdbGgQI , s, 2007)
(3hgcPG LGAJ gPI GdOQGSI dJhVM GhdG (B: (3fTGI eaGgje GdOjebQGWjI (B: (3GdJYOOjI GdSjGSjI (B.(3JOGhd GdSdWI ai GdacQ GdZQHi hJMOjO eaghe ebUhOgG heQGejgG dOjg hNUGFUgG heRGjGgG hYjhHgG hGNJdGa GdacQ GdOjbQGWi MhdgG Ke KGfjG hYdi VD Pdc HfjJ GdOQGSI Gf GZdH GdJjGQGJ GdGSdGejI bO bHdj GdfXQjI GdOjebQGWjI (B: (3hGdJYOOjI GdSjGSjI (B: (3hJOGhd GdSdWI ShGA ai GdOhdI GdGSdGejI Gh GdYdeGfjI (B.s
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdYGe (B2007s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdOSJhQjs; (3GdJYOOjI GdSjGSjI hJOGhd GdSdWIs; (3fXGe GdOjebQGWis; (3fXGe GdSjGSi GSdGeis; (3QSGFd LGeYjI s -- (3LGeYI GdbGgQI s -- (3cdjI GdLbhbs